Financial Decisions and Firm Value in the Food and Beverage Industry: Keputusan Keuangan dan Nilai Perusahaan dalam Industri Makanan dan Minuman - Umi Khabibah; Imelda Dian Rahmawati (Academia Open, 2022)
This study investigates the relationship between dividend policy, debt policy, managerial ownership, and firm value in the food and beverage companies listed on the Indonesia Stock Exchange from 2016 to 2019. The purposive sampling method was employed, and a total of 13 companies were included in the analysis. Secondary data was collected and analyzed using multiple linear regression. The findings reveal that dividend policy, debt policy, and managerial ownership significantly affect firm value in the food and beverage sector. Specifically, the study highlights that dividend policy, debt policy, and managerial ownership have positive effects on firm value. These findings contribute to the understanding of financial decision-making in the food and beverage industry, providing valuable insights for managers, investors, and policymakers seeking to enhance firm value and financial performance. Highlights: Dividend policy's impact: The study establishes a significant relationship between dividend policy and firm value in the food and beverage sector. Debt policy's influence: The research reveals the effect of debt policy on company value, providing insights into financial decision-making in the industry. Managerial ownership's significance: The study highlights the importance of managerial ownership and its impact on firm value in food and beverage companies. Keywords: Dividend policy, Debt policy, Managerial ownership, Firm value, Food and beverage sector.